2018
DOI: 10.1007/s13203-018-0195-8
|View full text |Cite
|
Sign up to set email alerts
|

Reaction kinetics of ethane partial oxidation to acetic acid

Abstract: The partial oxidation of ethane to ethylene and acetic acid on supported MoVNbPd/TiO 2 (P25 of Degussa) has been investigated. Pd was added in a nano-metallic form. The catalyst composition was also different from similar studied catalysts. This results in a better selectivity towards acetic acid formation. The reaction was carried out in a tubular reactor at temperature range 225-275 °C, total pressure range 0-200 psig and oxygen percentage in the feed gas of 10-40%. The feed gas contains ethane and oxygen. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Several sets of sequences of elementary steps have been proposed in the literature for ODHE over supported vanadia, 5,7‐11,50 MoVNb, 51,52 and MoVTeNbO catalysts 21,31‐34,53,54 . We propose herein a sequence of elementary steps (Table 1) that under certain conditions reduces to an expression that is first order in ethane and zero order in oxygen and water, consistent with reaction orders measured experimentally.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Several sets of sequences of elementary steps have been proposed in the literature for ODHE over supported vanadia, 5,7‐11,50 MoVNb, 51,52 and MoVTeNbO catalysts 21,31‐34,53,54 . We propose herein a sequence of elementary steps (Table 1) that under certain conditions reduces to an expression that is first order in ethane and zero order in oxygen and water, consistent with reaction orders measured experimentally.…”
Section: Resultssupporting
confidence: 80%
“…ODHE rates were found to be first order in ethane and zero order in oxygen at three different partial pressures of ethane (6-30 kPa) (Figure 3), analogous to the report of Annamalai et al in which ODHE rates were found to increase linearly with ethane partial pressure and to be invariant in oxygen partial pressure. 21 Several sets of sequences of elementary steps have been proposed in the literature for ODHE over supported vanadia, 5,[7][8][9][10][11]50 MoVNb, 51,52 and MoVTeNbO catalysts. 21,[31][32][33][34]53,54 We propose herein a sequence of elementary steps (Table 1) that under certain conditions reduces to an expression that is first order in ethane and zero order in oxygen and water, consistent with reaction orders measured experimentally.…”
Section: Odhe Kinetic Modelmentioning
confidence: 99%
“…The following references appear in the supplemental information : Al-Mayman et al., 2018 ; Barecka et al., 2017 ; BP, 2020 ; Brown, 2019 ; Business Insider, 2020 ; Chandel and Williams, 2009 ; Cheung et al, 2003 ; Cucchiella et al., 2017 ; Eckert et al, 2003 ; Eurostat, 2019 ; Fu et al., 2010 ; Garside, 2018 , 2020 ; Guilera et al., 2020 ; Hiller et al., 2003 ; International Energy Agency, 2019 ; International Renewable Energy Agency, 2019 ; Luyben and Tyréus, 1998 ; Metz et al., 2005 ; Montebelli et al., 2015 ; Nexant, 2018 ; Peschel, 2012 ; Rebsdat and Mayer, 2003 ; Shell South Africa, 2020 ; Wang et al., 2013 ; Wiser and Bolinger, 2019 .…”
Section: Supporting Citationsmentioning
confidence: 99%
“…Mo-V-M-O (M = Al, Fe, Cr or Ti) complex metal oxide catalysts were also tested [23]. Mo-V materials, frequently doped with other elements, supported on silica [24] and titania [25][26][27][28][29][30] were also described. Molybdo(vanado)phosphoric heteropoly acids with Keggin structure on oxide supports (SiO 2 , Al 2 O 3 , TiO 2 ) are found in the literature [31].…”
Section: Introductionmentioning
confidence: 99%